Correlation of Exercise Intensity on Blood Fibrinogen Levels - Adila Purnama Putri; Sulasmi Sulasmi (Jurnal Impresi Indonesia, 2025)
Fibrinogen is the main coagulation protein in the blood that plays a role in platelet clot formation. Increased fibrinogen levels in the blood are one of the important parameters for heart disease risk. Increased fibrinogen levels can be influenced by sports activities. The purpose of this study was to determine the correlation of exercise intensity to blood fibrinogen levels. This study used observational analytic research design with cross-sectional research type. The subjects in this study were members of the National STIKES Basketball Team who were grouped based on Maximum Heart Rate (MHR) measurements. The sampling technique of this study was purposive sampling, namely venous blood from members of the National STIKES Basketball Team. MHR measurement was carried out with a digital tensimeter and measurement of fibrinogen levels using the Stago STart Max tool at the Surakarta Prodia Clinical Laboratory. The research data obtained were analyzed using the Independent Sample T-Test test with the SPSS program for windows 11. The results of the Shapiro-Wilk normality test were obtained with a sig. p>0.05; homogeneity of variance test using the Levene Test with a sig value. 0.259 > p 0.05; Independent Sample T-Test test shows sig. (2-tailed) 0.000 <0.05. It can be concluded that there is a correlation between exercise intensity and blood fibrinogen levels.